(1,2) - Domination in the Total Graphs of Cn , Pn and K1,n - Nair, Deepa. S.; Murugesan, N. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we discuss the (1,2) - domination in the total graphs of Cn , Pnand K1,n